New insights into earthquake precursors from InSAR - Moro, Marco (Sci Rep, 2017)
We measured ground displacements before and after the 2009 L’Aquila earthquake using multi-temporal InSAR techniques to identify seismic precursor signals. We estimated the ground deformation and its temporal evolution by exploiting a large dataset of SAR imagery that spans seventy-two months before and sixteen months after the mainshock. These satellite data show that up to 15 mm of subsidence occurred beginning three years before the mainshock. This deformation occurred within two Quaternary basins that are located close to the epicentral area and are filled with sediments hosting multi-layer aquifers. After the earthquake, the same basins experienced up to 12 mm of uplift over approximately nine months. Before the earthquake, the rocks at depth dilated, and fractures opened. Consequently, fluids migrated into the dilated volume, thereby lowering the groundwater table in the carbonate hydrostructures and in the hydrologically connected multi-layer aquifers within the basins. This process caused the elastic consolidation of the fine-grained sediments within the basins, resulting in the detected subsidence. After the earthquake, the fractures closed, and the deep fluids were squeezed out. The pre-seismic ground displacements were then recovered because the groundwater table rose and natural recharge of the shallow multi-layer aquifers occurred, which caused the observed uplift.